2020
DOI: 10.1039/d0ra07318k
|View full text |Cite
|
Sign up to set email alerts
|

Injectable microfluidic hydrogel microspheres based on chitosan and poly(ethylene glycol) diacrylate (PEGDA) as chondrocyte carriers

Abstract: Chitosan/PEGDA double-network hydrogel microspheres prepared by microfluidic method as chondrocyte carriers for bottom-up cartilage tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…Subsequently, a novel kind of porous PLGA/chitosan polyelectrolyte complex MC was developed by electrostatic interaction using the emulsion-solidification technique combined with freeze-drying for its simple operation and easy scalability [ 144 ]. Another study that attempted to address the poor mechanical properties of chitosan, involved preparation of size-controllable chitosan/PEGDA hydrogel MCs using a water-in-oil approach after photo-crosslinking and physical-crosslinking, results showed that these cell-laden MCs were self-assembled into a 3D cartilage-like scaffold [ 145 ]. Furthermore, many studies have indicated that the physical properties of chitosan were mainly affected by the molecular weight, the sequence of the acetamido/amino groups, and the purity of the product [ 146 , 147 ].…”
Section: Appropriate Materials For Microcarriers In Cartilage Tementioning
confidence: 99%
“…Subsequently, a novel kind of porous PLGA/chitosan polyelectrolyte complex MC was developed by electrostatic interaction using the emulsion-solidification technique combined with freeze-drying for its simple operation and easy scalability [ 144 ]. Another study that attempted to address the poor mechanical properties of chitosan, involved preparation of size-controllable chitosan/PEGDA hydrogel MCs using a water-in-oil approach after photo-crosslinking and physical-crosslinking, results showed that these cell-laden MCs were self-assembled into a 3D cartilage-like scaffold [ 145 ]. Furthermore, many studies have indicated that the physical properties of chitosan were mainly affected by the molecular weight, the sequence of the acetamido/amino groups, and the purity of the product [ 146 , 147 ].…”
Section: Appropriate Materials For Microcarriers In Cartilage Tementioning
confidence: 99%
“…Lin et al. used microfluidic technology to prepare chitosan/PEGDA hydrogel microspheres (CP-MSSs) with controllable size via the oil-in-water method after photo-crosslinking and physical crosslinking [ 121 ]. The results showed that cp-MSSs loaded with chondrocytes could be used for injection, and the cell viability was still high after injection.…”
Section: Microsphere Processing Materialsmentioning
confidence: 99%
“…Therefore, it is difficult to synthesize nanodrugs with the same qualities quickly, accurately and repeatedly. Microfluidic technology might help solve the problem of inconsistent effects from laboratory research to clinical experiments given its high-speed self-assembly, narrow size distribution, and good repeatability [ 229 ].…”
Section: Clinical Application and Translationmentioning
confidence: 99%